A Handbook and Reader of Ottoman Arabic - Wagner, Esther-Miriam (Cambridge Semitic Languages and Cultures, 2021)
"Written forms of Arabic composed during the era of the Ottoman Empire present an immensely fruitful linguistic topic. Extant texts display a proximity to the vernacular that cannot be encountered in any other surviving historical Arabic material, and thus provide unprecedented access to Arabic language history. This rich material remains very little explored. Traditionally, scholarship on Arabic has focussed overwhelmingly on the literature of the various Golden Ages between the 8th and 13th centuries, whereas texts from the 15th century onwards have often been viewed as corrupted and not worthy of study. The lack of interest in Ottoman Arabic culture and literacy left these sources almost completely neglected in university courses. This volume is the first linguistic work to focus exclusively on varieties of Christian, Jewish and Muslim Arabic in the Ottoman Empire of the 15th to the 20th centuries, and present Ottoman Arabic material in a didactic and easily accessible way. Split into a Handbook and a Reader section, the book provides a historical introduction to Ottoman literacy, translation studies, vernacularisation processes, language policy and linguistic pluralism. The second part contains excerpts from more than forty sources, edited and translated by a diverse network of scholars. The material presented includes a large number of yet unedited texts, such as Christian Arabic letters from the Prize Paper collections, mercantile correspondence and notebooks found in the Library of Gotha, and Garshuni texts from archives of Syriac patriarchs."